Rac1 and RhoA differentially regulate angiotensinogen gene expression in stretched cardiac fibroblasts - Verma, Suresh K. (Oxford University Press, 2011)
AIMS: Angiotensin II (Ang II) stimulates cardiac remodelling and fibrosis in the mechanically overloaded myocardium. Although Rho GTPases regulate several cellular processes, including myocardial remodelling, involvement in mediating mechanical stretch-induced regulation of angiotensinogen (Ao), the precursor to Ang II, remains to be determined. We, therefore, examined the role and associated signalling mechanisms of Rho GTPases (Rac1 and RhoA) in regulation of Ao gene expression in a stretch model of neonatal rat cardiac fibroblasts (CFs). METHODS AND RESULTS: CFs were plated on deformable stretch membranes. Equiaxial mechanical stretch caused significant activation of both Rac1 and RhoA within 2–5 min. Rac1 activity returned to control levels after 4 h, whereas RhoA remained at a high level of activity until the end of the stretch period (24 h). Mechanical stretch initially caused a moderate decrease in Ao gene expression, but was significantly increased at 8–24 h. RhoA had a major role in mediating both the stretch-induced inhibition of Ao at 4 h and the subsequent upregulation of Ao expression at 24 h. β(1) integrin receptor blockade by Tac β(1) expression impaired acute (2 and 15 min) stretch-induced Rac1 activation, but increased RhoA activity. Molecular experiments revealed that Ao gene expression was inhibited by Rac1 through both JNK-dependent and independent mechanisms, and stimulated by RhoA through a p38-dependent mechanism. CONCLUSION: These results indicate that stretch-induced activation of Rac1 and RhoA differentially regulates Ao gene expression by modulating p38 and JNK activation.